Processing-driven structure-activity relationships of Polygonatum rhizome polysaccharides: From traditional processing to microbial fermentation - Mengshi Xiao; Zhili Yu; Jiuxiang Nie; Yuping Wei; Lin Zhang; Haijin Mou; Qiuhong Niu (Food Research International, 2026)

Molecular characterization and preliminary functional analysis of the NLRP3 inflammasome in golden pompano (Trachinotus ovatus) in response to Streptococcus agalactiae infection - Zhengjing Lin; Xuemei Mou; Peng Xu; Kianann Tan; Ting Huang; Renjie Li; Shuo Hu; Xiaoxin Huang; Sisi Huang; Lanfang Dong; Xiaohui Cai (Fish & Shellfish Immunology, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Mechanically evolving and solvent-responsive waste-valorized poly (methacrylated β-keratin) organogel nanostructures and exogel spatiotemporal transition property - Yoobsan Ejeta Amensisa; Chia-Kuan Lin; Chih-Chia Cheng; Chang-Mou Wu; Chien-Hsing Lu; Jem-Kun Chen (Chemical Engineering Journal, 2026)

Interferon-tau regulates the PGE2/PGF2α ratio via ISG15 in the goat corpus luteum during early pregnancy - Chunmei Shang; Haokun Liu; Zuhui Li; Yuanmeng Mou; Chenling Fan; Shan Liu; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Microbial carbon use efficiency and necromass turnover drive persistent carbon formation in paddy soils under straw-returned complex rotation - Yinhang Xia; Jun Chen; Donghai Jiang; Jiao Lin; Yan Xiao; Yongxue Yan; Tingsen Mou; Yeqin Shu; Nader Saad Elsayed; Yumei Chen; Georg Guggenberger; Zhenhua Zhang (Soil and Tillage Research, 2026)

A Model-based Harmonization Strategy of Standard Uptake Values for Paired PET Studies - Tian Mou; Yuejie Lin; Fanghui Fan; Jian Huang; Taotao Sun; En-Tao Liu; Yi Gao (Phenomics, 2026)

Unveiling deep-sea benthic biodiversity in the northern South China Sea through environmental DNA metabarcoding - Yaqin Huang; Kun Liu; Qianyong Liang; Heshan Lin; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Xuebao He; Zhongbao Li (Frontiers in Marine Science, 2026)
The northern South China Sea hosts highly heterogeneous deep-sea habitats, dotted with numerous active cold seeps and associated chemosynthetic ecosystems, while the Qiongdongnan Basin represents one of the most important natural gas hydrate accumulation regions in this area. Benthic fauna are core components sustaining deep-sea ecosystem stability and function, yet the biodiversity and community structure of benthic assemblages in this hydrate-rich basin remain poorly documented, creating a critical knowledge gap that hinders the ecological risk assessment and sustainable exploitation of local gas hydrate resources. Using environmental DNA (eDNA) metabarcoding, this study systematically investigated benthic biodiversity, community structure, and underlying assembly mechanisms across three representative habitat types in the Qiongdongnan Basin: cold seeps (CSs), gas hydrate stable zones (GHSZs), and non-gas hydrate stable zones (Non-GHSZs). A total of 334 benthic faunal species belonging to 275 genera, 167 families, 78 orders, 29 classes, and 19 phyla were recovered across all samples. Benthic genus richness peaked in GHSZs (191 genera), followed by CSs (184 genera), and was lowest in Non-GHSZs (176 genera). Community composition exhibited clear habitat-specific partitioning: GHSZ assemblages were dominated by Nematoda, Annelida, and Nemertea; Non-GHSZ assemblages were dominated by Nematoda, Echinodermata, and Annelida; and CS assemblages were dominated by Annelida, Echinodermata, and Mollusca. PERMANOVA confirmed significant overall differences in benthic community composition among the three habitats, with pairwise tests identifying CSs as the primary driver of inter-habitat dissimilarity. Integrated analyses using neutral community models and null models further revealed that deterministic processes. particularly variable selection, overwhelmingly governed benthic community assembly, while stochastic processes such as ecological drift and homogenizing dispersal played only a minor role. Environmental driver analysis indicated that benthic community variation in non-seep habitats (GHSZs and Non-GHSZs) was primarily modulated by sediment grain-size parameters and bottom-water salinity, whereas CS community structure was strongly correlated with sediment total organic carbon, sand content, and local meiobenthos density. This study provides a systematic eDNA-based assessment of benthic biodiversity across contrasting deep-sea habitats in the hydrate-bearing Qiongdongnan Basin and contributes a regional biodiversity baseline to support future ecological conservation, environmental impact assessment, and sustainable natural gas hydrate exploration and exploitation.

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Alginate-based composite hydrogel derived from Azotobacter vinelandii Av1: Preparation, properties, and wound-healing efficacy - Peng Yang; Rongqiang Chen; Siyuan Peng; Lin Zhu; Yifei Chang; Zhi Bao; Xiaodan Fu; Mengshi Xiao; Min Yang; Haijin Mou (Carbohydrate Polymers, 2026)

Potential Impact of Macromolecular Structure and Nanoscale Pore on Coal Matrix Subjected to Microwave–LN2 Freeze–Thaw Cycles - Xi Wu; He Li; Huihui Liu; Quanle Zou; Jiexin Lu; Junhui Mou; Baiquan Lin; Wei Yang; Jieyan Cao (Natural Resources Research, 2026)

Streptococcus thermophilus: A next-generation chassis for customizing exopolysaccharide with rare sugar - Mengshi Xiao; Jiuxiang Nie; Xiaodan Fu; Lin Zhang; Haijin Mou; Qiuhong Niu (Food Research International, 2026)

Life cycle assessment of a food waste-based biorefinery: From production of biopolymers to fabrication of advanced nanofibre masks - Jia-Le Zhu; Zi-Hao Qin; Johnny Sik Chun Lo; Zhen-Yao Wang; Jin-Hua Mou; Anda Fridrihsone; Zheng Sun; Carol Sze Ki Lin (Journal of Cleaner Production, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Innovative cellulose-based porous matrix loaded with carvacrol microemulsion for sustainable mango preservation - Linyun Mou; Jianlong Li; Ya Lu; Lin Wu; Guijun Bu; Juan Li; Ganpeng Li (International Journal of Food Microbiology, 2025)

Rational module substitution strategy to enhance ACE-inhibitory peptide activity - Qingping Liang; Siyuan Peng; Zhemin Liu; Jia Wang; Luying Tang; Changliang Zhu; Lin Zhu; Min Yang; Dongyu Li; Haijin Mou (Food Chemistry, 2025)

Functional characterization of the heat shock protein gene hsp78 in regulating carotenoid biosynthesis in the edible-medicinal fungus Cordyceps militaris - Zi-Qing Liang; Yi Zhao; Yong-Zhi Tan; Jie Wang; Yi-Lu Shao; Qian-Wang Zheng; Yuan Zou; Jun-Fang Lin; Mou-Tong Chen; Zhi-Wei Ye (Food Bioscience, 2025)

BreathFIT: Liquid metal-PDMS sticky conductors and AuNPs/MXene biosensors for synchronous EMG-lactate monitoring in respiratory health - Yang Liu; Zixin Lin; Yuetao Zhang; Xinyu Zhang; Zhiqi Li; Rubing Xiong; Chunxiao Long; Jiaqi Huang; Can Liu; Ziwei Zheng; Dan Li; Yongchang Ouyang; et al. (Chemical Engineering Journal, 2025)

Coconut shell inspired coating for impact-resistant and corrosion-protection of oil and gas pipelines - Zhengyu Liu; Li Zhang; Chenglong Mou; Xueqian Cao; Lin Chen; Guangan Zhang; Qunji Xue (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Machine learning-enhanced microfluidic CircRNA detection platform for high-accuracy breast cancer diagnosis - Xinyu Zhang; Zixin Lin; Huanyu Zhou; Qitao Xie; Yuetao Zhang; Yongmei Chen; Zijie Li; Runlin Lv; Zhiqi Li; Rubing Xiong; Xiaman Chen; Yong Xia; et al. (Chemical Engineering Journal, 2025)

Size-independent thermal tolerance enhancement in hybrid Abalone (Haliotis discus hannai × H. fulgens) under high-temperature acclimation - Shuyi Zhang; Jianfeng Mou; Yaqin Huang; Ronghui Zheng; Jun Bo; Youling Ye; Kun Liu; Heshan Lin (Aquaculture International, 2025)

Sediment characteristics affecting natural radionuclide distribution and radiological assessment in a tropical wetland near Maanshan Nuclear Power Plant, Southern Taiwan - Ting-Chien Chen; Yi-Lung Yeh; Fan-Cheng Zeng; Chih-Chung Lin; Zhi-Mou Chen; Wei-Hsiang Huang (Environmental Monitoring and Assessment, 2025)

Ribociclib derivative Rib-CA suppresses breast cancer progression via p53-dependent apoptosis - Mengwei Song; Ying Zhou; Xudong Yu; Boyu Zhang; Sen Wang; Kadirya Asan; Zihao Yang; Haiyan Lin; Jian Wang; Xiaoxue Song; Yongyuan Jiang; Si Chen; et al. (Toxicology and Applied Pharmacology, 2025)

Geochemical characteristics of Longtan transitional shale gas in the western Hubei Basin, northwest Middle Yangtze Block: Implications for the origin and carbon isotopes - Weiqing Liu; Haiyang Li; Yu Qiao; Wei Wu; Jienan Pan; Chuanlong Mou; Jianxin Yao; Yao Chen; Changsong Lin (Organic Geochemistry, 2025)

Harnessing basic helix-loop-helix-mediated transcriptional reprogramming in mixotrophic Chlorella for synergistic carbon waste remediation and biofuel production - Yu-Feng Yang; Jin-Hua Mou; Yu-Cheng Yang; Lan-Lan Hu; Wen-Li Huang; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2025)

Multi-channel thermal conductive phosphor-in-glass film with a record laser power density threshold for laser lighting - Hao Cheng; Yang Wang; Jiuzhou Zhao; Qing Wang; Shisheng Lin; Jiaxin Liu; Yun Mou; Lei Nie; Mingxiang Chen; Zhen Zhang; Yang Peng; Daqin Chen (Chemical Engineering Journal, 2025)

Dissolved organic matter-mediated metabolic shifts in Chlorella sorokiniana enhanced bioremediation of multi-ionic stress - Ting-Bin Hao; Zhong-Hong Zhang; Lan-Lan Hu; Si-Fen Liu; Jin-Hua Mou; Peizeng Yang; Zhiguo Yuan; Qi Zhang; Srinivasan Balamurugan; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; et al. (Journal of Hazardous Materials, 2025)

Ultra-linear, highly sensitive fabric strain/temperature sensor via the regulation of reduced graphene oxide defect and carrier migration for physiological risk alerts - Jianhong Hao; Shaowen Mou; Xinchen Wang; Ziyuan Zhou; Zihan Lin; Zhitong Wang; Linfei Zhao; Xiaowen Zhu; Shukang Cao; Zhangling Duan; Weiqiang Hong; Qi Hong; et al. (Chemical Engineering Journal, 2025)

Microcystis aeruginosa co-exposure to bisphenol AF and perfluorooctanoic acid promotes cell division and increases microcystin and nitrous oxide emissions - Hao Ming; Jinhua Mou; Carol Sze Ki Lin; Liandong Zhu (Chemical Engineering Journal, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Whole-genome sequences revealed genomic diversity and selection signatures of Dermacentor silvarum in Shaanxi, China - Yi-yao Mou; Meng-ke Lin; Yu-ying Yang; Yu-kun Kang; Ya-qing Li; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

A bifunctional fluorescent gel for sensitive visual/fluorescent dual-mode detection and efficient adsorption of Pb2+ from wastewater - Yinhui Zhang; Mengshi Mou; Lin Dong; Hongmei Yu (Journal of Water Process Engineering, 2025)

Understanding tractography in edematous brain regions: challenges and solutions - Shin Tai Chong; Joseph Yuan-Mou Yang; Ching-Po Lin (Brain Structure and Function, 2025)

F- dopants blocking hydroxyl interference: A facile solution for realizing humidity-resistive, selectivity adjustable, highly sensitive In2O3-based gas sensors - Zhidong Jin; Yue Mou; Jinbo Zhao; Fei Liu; Lin Liu; Jiurong Liu; Shiqiang Li; Fenglong Wang; Zhou Wang; Lili Wu (Chemical Engineering Journal, 2025)

Design of technical Ni@Silicate-1 catalysts for dry reforming of methane - Zhaomin Gao; Mengyang Cai; Jikai Zhang; Jiachen Wang; Chunyan Liu; Peng Guo; Xiaoling Mou; Ronghe Lin; Jiaxu Liu (Chemical Engineering Journal, 2025)

Triethoxysilane-enhanced graphene/carbon nanoparticles conductive network for multifunctional fabric electronics with pressure, temperature and strain sensing capabilities - Yunong Zhao; Jianhong Hao; Zihan Lin; Shaowen Mou; Shujing Feng; Fan Yao; Ziyuan Zhou; Zhitong Wang; Zhaobin Li; Xianghui Li; Xiaowen Zhu; Tianxu Zhang; et al. (Chemical Engineering Journal, 2025)

Harnessing oleaginous protist Schizochytrium for docosahexaenoic acid: Current technologies in sustainable production and food applications - Zongfan Peng; Liang Zhong; Yuqin Li; Siran Feng; Jinhua Mou; Yahui Miao; Carol Sze Ki Lin; Zhenyao Wang; Xuan Li (Food Research International, 2025)

An arabinogalactan from Lycium barbarum mitigated DSS caused intestinal injury via inhibiting mucosal damage and regulating the gut microbiota disorder - Jiaojiao Mou; Jie Yang; Yanying Sun; Jing Liu; Yuxin Zhao; Hong Lin; Jianjun Yang (Carbohydrate Polymers, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

Anti-sediment wear coupled corrosion protective coating for oil and gas exploitation pipeline protection - Zhengyu Liu; Jingzhou Liu; Chenglong Mou; Li Zhang; Xueqian Cao; Lin Chen; Guangan Zhang; Qunji Xue (Chemical Engineering Journal, 2025)

Sucrose non-fermenting 1-related protein kinase 2–14 participating in lipid elevating efficacy and biodiesel upgrade by Coccomyxa subllipsoidea - Yuanyuan Luo; Sisi Zhao; Zhixuan Fan; Yuqin Li; Zongfan Peng; Yulong Zhang; Siran Feng; Jinhua Mou; Zhenyao Wang; Carol Sze Ki Lin; Xuan Li (Chemical Engineering Journal, 2025)

A fully integrated, non-invasive, and multimodal wearable device for sweat stimulation, collection and multiple physiological signals analysis - Yuetao Zhang; Zijie Li; Xuejiao Fan; Yan Liu; Zhiqi Li; Ziwei Zheng; Zixin Lin; Wenshan Zhang; Qingci Mu; Guangquan Mo; Yong Xia; Lei Mou (Chemical Engineering Journal, 2025)

Status and Evolving Characteristics of Marine Spatial Resources in the Hangzhou Bay Area of Zhejiang Province, China - Peng Wang; Jingru Zhou; Kaixuan Zheng; Xia Lin; Mou Leong Tan; Jingchao Shi; Xingwen Lin; Xihe Yue; Xu Ma; Fei Zhang (Journal of Marine Science and Engineering, 2025)
The 20th Party Congress initiated efforts to strengthen maritime power and advance marine ecological civilization, which is essential for promoting sustainable development. To achieve this goal, this study combines field measurements, drone imagery, and high-resolution remote sensing data, using GIS technology to analyze changes in marine resources in Hangzhou Bay and assess marine area usage, intertidal zone area changes, and coastline erosion. The key findings show that the industrial sector accounts for the largest usage of marine area, with the industrial sea area growing by 110.3% from 2018 to 2020. The diversity index for marine area usage in Hangzhou Bay has remained stable, consistently at 0.6 and above over the past five years. The continental coastline of Hangzhou Bay has shown a decreasing trend in recent years from 2018 and 2021, with a total intertidal area of Hangzhou Bay decreased by 73.44 km2, where the overall shoal pattern in Hangzhou Bay remained relatively stable from 2008 to 2016. Erosion has been the predominant force, with maximum erosion surpassing 3 m and causing significant spatial changes. Between 2012 and 2016, the total erosion volume reached 192,473.74 × 106 m3, with an average annual erosion rate of 48,118.44 × 106 m3. This process has led to a gradual reduction in the size of affected areas over the period from 2001 to 2021. This research provides valuable insights for authorities to make informed decisions regarding the management of marine spatial resources in Hangzhou Bay.

Structural characterization and prebiotic activity evaluation of novel fucosylated disaccharides prepared from bacterial exopolysaccharides - Shihao Nan; Xinmiao Ren; Mengshi Xiao; Lin Zhu; Haijin Mou; Ningyang Li; Rong Li; Shaoping Nie; Xiaodan Fu (Food Bioscience, 2024)

Environmental benefits of valorising food waste into bio-based polyols for the production of polyurethane rigid foams - Zi-Hao Qin; Anda Fridrihsone; Liang Dong; Jin-Hua Mou; Yahui Miao; Lin Zhang; Chunbao Xu; Mikelis Kirpluks; Carol Sze Ki Lin (Sustainable Production and Consumption, 2024)

Multiple environmental gradients shape the functional structure of macrobenthic communities across the Pacific Arctic shelf - Kun Liu; Yaqin Huang; Weibo Wang; Jianfeng Mou; Junhui Lin; Shuyi Zhang; Longshan Lin; Jun Sun; Zhongyong Gao; Heshan Lin; Xuebao He (Science of The Total Environment, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Impact of NaCl perturbation on physicochemical and structural properties of preheat–treated egg white protein modulating foaming property - Yiwen Ding; Nan Xiao; Shanguang Guo; Junhao Lin; Lintao Chen; Xiangwei Mou; Minmin Ai (Food Chemistry, 2024)

Electronic effect in bromide-modified noble metal catalysts promotes highly stable and selective hydrogenation - Xintai Chen; Mengqi Yang; Qiying Liu; Xiaoling Mou; Linbin Ying; Yu Meng; Ronghe Lin; Yunjie Ding (Chemical Engineering Journal, 2024)

Anchoring Ni atomic clusters on yolk-shell In2O3 microspheres for highly sensitive, ultra-rapid responding/recovering ppb-level NO2 detections - Zhidong Jin; Yue Mou; Jinbo Zhao; Fei Liu; Lin Liu; Dewen Zhao; Shiqiang Li; Jiurong Liu; Lili Wu (Chemical Engineering Journal, 2024)

Assessment of solar geoengineering impact on precipitation and temperature extremes in the Muda River Basin, Malaysia using CMIP6 SSP and GeoMIP6 G6 simulations - Mou Leong Tan; Yi Lin Tew; Juneng Liew; Govindasamy Bala; Mari R. Tye; Chun Kiat Chang; Nurfashareena Muhamad (Science of The Total Environment, 2024)

Co-pyrolytic drivers and volatiles of 3D printing waste and textile dyeing sludge and their multi-objective optimization - Ziting Lin; Xiaoming Li; Jingfang Mou; Fatih Evrendilek; Jingyong Liu; Jiayu Liang; Sen Lin; Haiming Cai; Yao He; Guanzheng Zhuang; Chunxiao Yang (Chemical Engineering Journal, 2024)

Valorisation of food waste into bio-based polyurethane rigid foams: From experimental investigation to techno-economic analysis - Zi-Hao Qin; Anda Fridrihsone; Jin-Hua Mou; Ralfs Pomilovskis; Daniela Godina; Yahui Miao; Ziyao Liu; Chi-Wing Tsang; Lin Zhang; Chunbao Xu; Shauhrat S. Chopra; Eliza Kaulina; et al. (Chemical Engineering Journal, 2024)

Utilization of tofu wastewater and Nannochloropsis oceanica for eutrophication mitigation and eicosapentaenoic acid valorization: Advancing carbon neutrality and resource recycling - Yuqin Li; Xing Meng; Zhenyao Wang; Xin Lin; Yuan Xu; Jinhua Mou; Rong Zhou; Yufang Tang; Carol Sze Ki Lin; Xuan Li (Chemical Engineering Journal, 2024)

Memristive switching in the surface of a charge–density–wave topological semimetal - Jianwen Ma; Xianghao Meng; Binhua Zhang; Yuxiang Wang; Yicheng Mou; Wenting Lin; Yannan Dai; Luqiu Chen; Haonan Wang; Haoqi Wu; Jiaming Gu; Jiayu Wang; et al. (Science Bulletin, 2024)

Environmental evaluation of emerging bakery waste oil-derived sophorolipids production by performing a dynamic life cycle assessment - Yahui Miao; Xiaomeng Hu; Ming Ho To; Huaimin Wang; Zihao Qin; Jinhua Mou; Wei Yan; Guneet Kaur; Sophie L.K.W. Roelants; Carol Sze Ki Lin; Shauhrat S. Chopra (Sustainable Production and Consumption, 2024)

Integrative informatics analysis identifies that ginsenoside Re improves renal fibrosis through regulation of autophagy - Yingying Liu; Lingyun Mou; Zhengzi Yi; Qisheng Lin; Khadija Banu; Chengguo Wei; Xiaoxia Yu (Journal of Natural Medicines, 2024)

The Impact of Offshore Photovoltaic Utilization on Resources and Environment Using Spatial Information Technology - Peng Wang; Jingru Zhou; Xinfei Jin; Jingchao Shi; Ngai Weng Chan; Mou Leong Tan; Xingwen Lin; Xu Ma; Xia Lin; Kaixuan Zheng; Jiexuan Wu; Fei Zhang (Journal of Marine Science and Engineering, 2024)
In recent years, the rapid development of the photovoltaic (PV) industry has resulted in a saturation of research on onshore PV power plant construction. However, current studies on the impact of marine PVs on the marine environment remain limited and scarce. In order to facilitate the implementation of carbon reduction goals and promote the sustainable development of the offshore PV industry, this study analyzes the environmental impact of PV sea-use resources based on spatial information technology in the western part of Gaotang Island. The findings show that the MIKE21FM model provides relatively accurate simulations of tidal flow and tide level in the marine PV area. Flow velocity in the marine PV area exhibits a decreasing trend, with an average decrease ranging from 0.03 to 0.07 m/s. This decrease minimally affects surrounding navigational channels and large-scale flow fields. The resulting siltation is also deemed less significant, with an annual deposition from 0.03 to 0.06 m/a. Moreover, offshore PV construction resulted in a total intertidal biological loss of 123.45 t. The suspension of sediment during cofferdam construction and removal has a potential effect on zooplankton and fishery resources. Overall, it is proposed that careful planning, prudent site selection, and the execution of countermeasures during marine PV construction will combine to minimize the impact on the marine environment.

Novel magnetic separable BiOBr@Fe3O4 p-n heterostructure with highly efficient photocatalytic property toward organic pollutants - Kebena Gebeyehu Motora; Chang-Mou Wu; Meng-Chi Chuang; Szu-Tsen Lin (Journal of Water Process Engineering, 2024)

An improved wind quality control for the China-France Oceanography Satellite (CFOSAT) scatterometer - Xiaoheng Mou; Wenming Lin (Acta Oceanologica Sinica, 2024)

Identification of microplastics in raw and treated municipal solid waste landfill leachates in Hong Kong, China - Zi-Hao Qin; Muhammad Ahmar Siddiqui; Xiayin Xin; Jin-Hua Mou; Sunita Varjani; Guanghao Chen; Carol Sze Ki Lin (Chemosphere, 2024)

Nexus of food waste and climate change framework: Unravelling the links between impacts, projections, and emissions - Sunita Varjani; Shaili Vyas; Junjie Su; Muhammad Ahmar Siddiqui; Zi-Hao Qin; Yahui Miao; Ziyao Liu; Shraya Ethiraj; Jin-Hua Mou; Carol Sze Ki Lin (Environmental Pollution, 2024)

Sustainable paramylon production from food waste by Euglena gracilis using a waste-based cell immobilisation technique - Jin-Hua Mou; Si-Fen Liu; Li-Li Yang; Zi-Hao Qin; Yu-Feng Yang; Zhen-Yao Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2024)

Food waste from various origins as feedstocks for recombinant protein production by Yarrowia lipolytica using in situ fibrous bed bioreactor - Jin-Hua Mou; Wei Yan; Zi-Hao Qin; Md Ariful Haque; Ya-Hui Miao; Feng-Xue Xin; Xiang Wang; Patrick Fickers; Carol Sze Ki Lin (Chemical Engineering Journal, 2024)

Host-derived peptide signals regulate Pseudomonas aeruginosa virulence stress via the ParRS and CprRS two-component systems - Ning-Lin Zhao; Zi-Qi Zhu; Han-Zhong Feng; Ying-Jie Song; Qin Huang; Xing-Yu Mou; Cheng Nong; Yong-Xing He; Rui Bao (Journal of Hazardous Materials, 2023)

Enhanced methane yield in anaerobic digestion of waste activated sludge by combined pretreatment with fungal mash and free nitrous acid - Min Zhang; Yuwei Yang; Huaqian Mou; Aodong Pan; Xiaomei Su; Jianrong Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2023)

High spatiotemporal resolution reconstruction of suspended particulate matter concentration in arid brackish lake, China - Changjiang Liu; Fei Zhang; Mou Leong Tan; Chi-Yung Jim; Kaishan Song; Jingchao Shi; Xingwen Lin; Hsiang-Te Kung (Journal of Cleaner Production, 2023)

Comparation of mesophilic and thermophilic anaerobic co-digestion of food waste and waste activated sludge driven by biochar derived from kitchen waste - Rong Zhang; Min Zhang; Huaqian Mou; Zijing An; Hailu Fu; Xiaomei Su; Chongjun Chen; Jianrong Chen; Hongjun Lin; Faqian Sun (Journal of Cleaner Production, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

Dihydromyricetin promotes GLP-1 release and glucose uptake by STC-1 cells and enhances the effects of metformin upon STC-1 cells and diabetic mouse model - Yuanzhi Yao; Xiaoying Li; Xiaoqin Yang; Hai Mou; Lin Wei (Tissue and Cell, 2023)

Controlled and driving mechanism of the SPM variation of shallow Brackish Lakes in arid regions - Changjiang Liu; Fei Zhang; Chi-Yung Jim; Verner Carl Johnson; Mou Leong Tan; Jingchao Shi; Xingwen Lin (Science of The Total Environment, 2023)

DIET-like mutualism of Geobacter and methanogens at specific electrode potential boosts production of both methane and hydrogen from propionate - Yuqing Yan; Jiayao Zhang; Lili Tian; Xuejun Yan; Lin Du; Aaron Leininger; Mou Zhang; Nan Li; Zhiyong Jason Ren; Xin Wang (Water Research, 2023)

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Novel Ag3PO4@ZIF-8 p-n heterojunction for effective photodegradation of organic pollutants - Kebena Gebeyehu Motora; Chang-Mou Wu; Szu-Tsen Lin (Journal of Water Process Engineering, 2023)

Environmental profiling microalgae-based eicosapentaenoic acid production along the technical advancement via life cycle assessment - Zi-Hao Qin; Xiaomeng Hu; Jin-Hua Mou; Guo-Hui He; Guang-Bin Ye; Hong-Ye Li; Shauhrat Singh Chopra; Liang Dong; Carol Sze Ki Lin; Xiang Wang (Journal of Cleaner Production, 2023)

Do tillage systems affect the cadmium threshold in farmland soil for environmental quality standard setting? - Zhaolin Du; Weiqiang Dou; Dasong Lin; Li Qin; Yi An; Hongan Chen; Lina Wu; Liyan Mou (Science of The Total Environment, 2023)

Aflatoxin B1 exposure triggers hepatic lipotoxicity via p53 and perilipin 2 interaction-mediated mitochondria-lipid droplet contacts: An in vitro and in vivo assessment - Lin Che; Jing Huang; Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Ze-Bang Du; Jia-Shen Wu; Zhong-Ning Lin; Yu-Chun Lin (Journal of Hazardous Materials, 2023)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Between the devil and the deep blue sea: Trends, drivers, and impacts of coastal reclamation in Malaysia and way forward - Su Yin Chee; Mou Leong Tan; Yi Lin Tew; Yee Kwang Sim; Jean Chai Yee; Amanda Kar Mun Chong (Science of The Total Environment, 2023)

Biofouling characteristics in Xinghua Bay of Fujian, China - Heshan Lin; Yaqin Huang; Yingyue Lin; Shuyi Zhang; Shihao Yu; Kun Liu; Jianfeng Mou; Junhui Lin; Xuebao He; Sujing Fu; Weijie Xie; Zhongbao Li (Frontiers in Marine Science, 2023)
Biofouling is one of the main factors affecting the efficiency and safety of cooling water systems in coastal nuclear power plants. Understanding the population dynamics, succession rules and cumulative effects of major fouling organisms is the basis for targeted prevention and control. A 1-year simulated concrete panel test was conducted from December 2020 to November 2021 in Xinghua Bay, China. A total of 78 species of fouling organisms were recorded by combining the monthly, seasonal, semiannual, annual and monthly cumulative panels, and the community composition was dominated by nearshore warm-water species, making for a typical subtropical inner bay-type community. The fouling organisms had a peak attachment period from June to October. Significantly more attachment was observed during summer (from June to August) than during the other three seasons. The attachment amount in the second half-year (from June to November) was much higher than that in the first half-year (from December to May). The attachment thickness, density, and biomass of the bottom summer panels reached 20 cm, 105,150 ind./m 2 , and 19,274.50 g/m 2 , respectively, while those of the bottom annual panels were 40 cm, 27,300 ind./m 2 , and 17,762.50 g/m 2 , respectively. The dominant fouling organisms with calcified shells mainly included Amphibalanus reticulatus and Pernaviridis . These species had high attachment amounts,could accumulate attachments for a long time, and even might cause secondary blockage, making them the most detrimental to the safety of a cooling system. Moreover,the seasonal upward growth of hydroids and bryozoans can also significantly reduce the efficiency of cooling water intake. We suggest that targeted prevention and control should be carried out according to the larval attachment period of different dominant groups of fouling organisms during June-October, which can greatly improve the prevention and control efficiency. Strengthening the research on the biological cycle phenomenon of the main species and their main environmental impact factors, and establishing a scientific and effective early-warning model are the governance direction of formulating and implementing scientific pollution prevention and control in the future.

Rose Bengal inhibits β-amyloid oligomers-induced tau hyperphosphorylation via acting on Akt and CDK5 kinases - Chen-Ye Mou; Yan-Fei Xie; Jia-Xin Wei; Qi-Yao Wang; Jing-Yang Le; Yong-Jie Bao; Pan-Pan Zhang; Yue-Chun Mao; Xing-Han Huang; Han-Bo Pan; C. Benjamin Naman; Lin Liu; et al. (Psychopharmacology, 2022)

Proteomic differences between Vibrio tubiashii strains with high- or low-virulence levels isolated from diseased ivory snail Babylonia areolata - Ruixuan Wang; Xiaojing Liu; Jiangyong Wang; Huizhu; Xiaozhi Lin; Jingfeng Sun; Hongli Mou; Ting Zhang; Xilan Ma (Aquaculture International, 2022)

The efficacy and safety of TNF inhibitor (golimumab) as salvage treatment in patients with refractory noninfectious uveitis - Yi Jin; Shanshan Lu; You Lin; Xiaoyue Mou (Inflammopharmacology, 2022)

8- O - β -D-Glucopyranosyl-2-methylchromone, a new chromone glycoside from the Tibetan medicine plant of Swertia punicea Hemsl - Lin-Yun Mou; Min Wei; Hai-Yan Wu; Li-Jiao Hu; Jian-Long Li; Gan-Peng Li (Natural Product Research, 2022)

Feasibility Research on Fish Pose Estimation Based on Rotating Box Object Detection - Bin Lin; Kailin Jiang; Zhiqi Xu; Feiyi Li; Jiao Li; Chaoli Mou; Xinyao Gong; Xuliang Duan (Fishes, 2021)
A video-based method to quantify animal posture movement is a powerful way to analyze animal behavior. Both humans and fish can judge the physiological state through the skeleton framework. However, it is challenging for farmers to judge the breeding state in the complex underwater environment. Therefore, images can be transmitted by the underwater camera and monitored by a computer vision model. However, it lacks datasets in artificial intelligence and is unable to train deep neural networks. The main contributions of this paper include: (1) the world’s first fish posture database is established. 10 key points of each fish are manually marked. The fish flock images were taken in the experimental tank and 1000 single fish images were separated from the fish flock. (2) A two-stage attitude estimation model is used to detect fish key points. The evaluation of the algorithm performance indicates the precision of detection reaches 90.61%, F1-score reaches 90%, and Fps also reaches 23.26. We made a preliminary exploration on the pose estimation of fish and provided a feasible idea for fish pose estimation.

Microplastics in Mollusks: Research Progress, Current Contamination Status, Analysis Approaches, and Future Perspectives - Ruixuan Wang; Hongli Mou; Xiaozhi Lin; Hui Zhu; Bing Li; Jiangyong Wang; Muhammad Junaid; Jun Wang (Frontiers in Marine Science, 2021)
Plastic fragments < 5 mm, known as microplastics (MPs), are ubiquitously present in the marine environment. Research on MPs pollution has gradually shifted from field investigations to laboratory studies. With the rapid growth of plastic consumption and the prevalence of aquaculture products, studies on marine MPs have focused on key marine species, such as mollusks. This review summarizes the recent knowledge including 77 important relevant literatures (from 2010 to 2021) on MPs contamination in mollusks with the objectives of (1) elucidating the current status of MPs pollution levels in mollusks, (2) highlighting the main methods and techniques for separation, extraction, and identification of MPs in soft tissues of bivalves and (3) presenting the current research progress and future directions. The review visually presents some of the important results in graphic form, which shows that the most common polymer plastics in bivalves are polypropylene, polystyrene, and polyethylene, and the shapes were mainly fiber and threadiness, mollusks are more likely to feed smaller MPs, most of the MPs in bivalves are less than 500 μm, and the abundance of MPs in seawater and the abundance of MPs in mollusks have a positive relationship, etc. This review will provide a comprehensive reference for studies of microplastics in marine organisms and the ecological pollution, and also has scientific guiding significance in the research method.

Numerical Analysis of the Water-blocking Performance of a Floor with a Composite Structure under Fluid–solid Coupling - Ang Li; Qian Mu; Li Ma; Chaoyang Liu; Shengquan Wang; Feng Wang; Lin Mou (Mine Water and the Environment, 2021)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Three new phenylacetamide glycosides from Dracocephalum tanguticum Maxim and their anti-hyperglycemic activity - En-Guang Ma; Hai-Yan Wu; Li-Jiao Hu; Min Wei; Lin-Yun Mou; Gan-Peng Li (Natural Product Research, 2020)

Data Analysis and Key Parameters of Typical Water Hazard Control Engineering in Coal Mines of China - Lin Mou; Shuning Dong; Wanfang Zhou; Wei Wang; Ang Li; Zhiyuan Shi (Mine Water and the Environment, 2020)

Two new xanthone glycosides from Swertia punicea Hemsl. and their anti-inflammatory activity - Lin-Yun Mou; Hai-Yan Wu; En-Guang Ma; Ming-Feng Wang; Yan-Qing Duan; Sheng Lei; Gan-Peng Li (Natural Product Research, 2020)

Chemical fingerprint and source apportionment of PM2.5 in highly polluted events of southern Taiwan - Huazhen Shen; Tsung-mou Yang; Chun-chung Lu; Chung-shin Yuan; Chung-Hsuang Hung; Chi-tsan Lin; Chia-wei Lee; Guohua Jing; Gongren Hu; Kuo-cheng Lo (Environmental Science and Pollution Research, 2020)

Macrobenthic communities on the continental shelf of the Prydz Bay, East Antarctica - Kun Liu; Heshan Lin; Xuebao He; Yaqin Huang; Zhong Li; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Jianjun Wang; Jun Sun (Acta Oceanologica Sinica, 2020)

Eco-friendly preparation of chitooligosaccharides with different degrees of deacetylation from shrimp shell waste and their effects on the germination of wheat seeds - Xiaodan Fu; Lin Zhu; Li Li; Tan Zhang; Meng Li; Haijin Mou (Marine Life Science & Technology, 2019)
Production of chitosan and its derivatives by traditional methods involves the excessive use of a reaction solution comprised of sodium hydroxide and hydrochloric acid. Waste water resulting from this process has limited the application of chitosan as a fertilizer as the process causes serious environmental pollution. Specifically, the resulting waste water contains high levels of dissolved nitrogen and minerals from shrimp shells. In this study, an eco-friendly method was established to produce chitooligosaccharides (COS) with different degrees of deacetylation (DDAs) from shrimp shell waste. At a solid-to-solvent ratio of 1:6, the degree of demineralization was above 90% with the treatment of 30 g·L −1 H 3 PO 4 , and the degree of deproteinization was above 80% when treated with 30 g·L −1 KOH at 70 °C. Chitosans with different DDAs were obtained by microwave-assisted KOH metathesis and the COS with Mw approximately 1500 Da were then prepared by oxidative degradation. In summary, 33.73 kg H 3 PO 4 , 12.77 kg, and 241.31 kg KOH were supplied during the processes of demineralization, deproteinization, and deacetylation of 100 kg shrimp shell waste, respectively. The process water was totally recycled, demonstrating that the shrimp shell could be wholly transformed into fertilizer. The entire process created a product with the fractions of N:P 2 O 5 :K 2 O:COS = 7.94:24.44:10.72:18.27. The test on the germination promotion of wheat seeds revealed that the COS with 72.12% DDA significantly promoted germination. This work demonstrated the use of an eco-friendly preparation method of COS with a specific degree of deacetylation that can be applied as a fertilizer.

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

Mechanical Evolution Mechanism of Coal and Gas Outburst - Huihui Liu; Baiquan Lin; Junhui Mou; Wei Yang (Rock Mechanics and Rock Engineering, 2019)

Spatial variability of macrobenthic production in the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Junhui Lin; Yaqin Huang; Xuebao He; Zhong Li; Shuyi Zhang; Jianfeng Mou; Yanguang Liu; Puqing Song; Yu Wang; et al. (Polar Biology, 2019)

Spatial pattern of macrobenthic communities along a shelf-slope-basin transect across the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Yaqin Huang; Zhong Li; Junhui Lin; Xuebao He; Shuyi Zhang; Jianfeng Mou; Yu Wang; Bingpeng Xing (Acta Oceanologica Sinica, 2018)

An ecological survey of the abundance and diversity of benthic macrofauna in Indonesian multispecific seagrass beds - Junhui Lin; Yaqin Huang; Ucu Yanu Arbi; Heshan Lin; Muhammad Husni Azkab; Jianjun Wang; Xuebao He; Jianfeng Mou; Kun Liu; Shuyi Zhang (Acta Oceanologica Sinica, 2018)

Fouling community characteristics in subtropical coastal waters of the southwestern East China Sea - Heshan Lin; Jianjun Wang; Wei Liu; Kun Liu; Shuyi Zhang; Xuebao He; Yaqin Huang; Junhui Lin; Jianfeng Mou; Chengxing Zheng; Tao Yan (Acta Oceanologica Sinica, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

Immune recovery after fluid resuscitation in rats with severe hemorrhagic shock - Feng Yao; Yuan-qiang Lu; Jiu-kun Jiang; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2017)

Nickel in milled rice ( Oryza sativa L.) from the three main rice-producing regions in China - Zhenzhen Cao; Renxiang Mou; Zhaoyun Cao; Xiaoyan Lin; Ping Xu; Zhijun Chen; Zhiwei Zhu; Mingxue Chen (Food Additives & Contaminants Part B-Surveillance, 2017)

Proteasomes regulate hepatitis B virus replication by degradation of viral core-related proteins in a two-step manner - Zi-Hua Zheng; Hui-Ying Yang; Lin Gu; Xiao-Mou Peng (Virus Genes, 2016)

Resting State fMRI Demonstrates a Disturbance of the Cerebello-Cortical Circuit in Essential Tremor - Wenjie Yin; Wei Lin; Wenbo Li; Shusen Qian; Xin Mou (Brain Topography, 2016)

Paleokarst crust of Ordovician limestone and its utilization in evaluating water inrushes in coalmines of North China - Gongyu Li; Lin Mou; Wanfang Zhou (Carbonates and Evaporites, 2015)

The anti-allergic activity of polyphenol extracted from five marine algae - Yu Chen; Hong Lin; Zhenxing Li; Quangui Mou (Journal of Ocean University of China, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

Wind wave characteristics and engineering environment of the South China Sea - Zhifeng Wang; Liangming Zhou; Sheng Dong; Lunyu Wu; Zhanbin Li; Lin Mou; Aifang Wang (Journal of Ocean University of China, 2014)

Expression of the HPV18E2 Gene in Cervical Cancer and Premalignant Lesions and its Clinical Significance - Ling Mou; Bin Wu; Ya Hu; Ying Lan; Feng-Lin Lv (Cell Biochemistry and Biophysics, 2014)

A physics-based dual-frequency approach for altimeter wind speed retrieval - Shuiqing Li; Liangming Zhou; Zhanbin Li; Qingsheng Miao; Lin Mou; Aifang Wang (Journal of Ocean University of China, 2014)

Menstrual blood-derived mesenchymal stem cells differentiate into functional hepatocyte-like cells - Xiao-zhou Mou; Jian Lin; Jin-yang Chen; Yi-fei Li; Xiao-xing Wu; Bing-yu Xiang; Cai-yun Li; Ju-ming Ma; Charlie Xiang (Journal of Zhejiang University-SCIENCE B, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Halohasta litorea gen. nov. sp. nov., and Halohasta litchfieldiae sp. nov., isolated from the Daliang aquaculture farm, China and from Deep Lake, Antarctica, respectively - Yun-Zhuang Mou; Xing-Xing Qiu; Mei-Lin Zhao; Heng-Lin Cui; Dickson Oh; Mike L. Dyall-Smith (Extremophiles, 2012)

Salinarchaeum laminariae gen. nov., sp. nov.: a new member of the family Halobacteriaceae isolated from salted brown alga Laminaria - Heng-Lin Cui; Xin Yang; Yun-Zhuang Mou (Extremophiles, 2011)

Effects of sediment burial disturbance on seedling survival and growth of Suaeda salsa in the tidal wetland of the Yellow River estuary - Zhigao Sun; Xiaojie Mou; Guanghui Lin; Lingling Wang; Hongli Song; Huanhuan Jiang (Plant and Soil, 2010)

Regulation of GSK-3 beta in the proliferation and apoptosis of human thyrocytes investigated using a GSK-3 beta-targeting RNAi adenovirus expression vector: involvement the Wnt/beta-catenin pathway - Gang Chen; Qiqin Jiang; Zhenhui You; Jin Yao; Lunpan Mou; Xu Lin; Xiaoyan Shen; Tingting You; Qiang Lin; Junping Wen; Lixiang Lin (Molecular Biology Reports, 2010)

Hypertonic saline resuscitation reduces apoptosis of intestinal mucosa in a rat model of hemorrhagic shock - Yuan-qiang Lu; Wei-dong Huang; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mou (Journal of Zhejiang University-SCIENCE B, 2008)

Generating oxidation-resistant variants of Bacillus kaustophilus leucine aminopeptidase by substitution of the critical methionine residues with leucine - Meng-Chun Chi; Wei-Mou Chou; Chih-Hsien Wang; Wenlung Chen; Wen-Hwei Hsu; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

A thermostable leucine aminopeptidase from Bacillus kaustophilus CCRC 11223 - Long-Liu Lin; Wen-Hwei Hsu; Cheng-Pu Wu; Meng-Chun Chi; Wei-Mou Chou; Hui-Yu Hu (Extremophiles, 2004)

Generating oxidation-resistant variants of Bacillus kaustophilus leucine aminopeptidase by substitution of the critical methionine residues with leucine - Meng-Chun Chi; Wei-Mou Chou; Chih-Hsien Wang; Wenlung Chen; Wen-Hwei Hsu; Long-Liu Lin (Antonie van Leeuwenhoek, 2004)